2019
DOI: 10.1177/1358863x19838350
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-accelerated thrombolysis (USAT) versus standard catheter-directed thrombolysis (CDT) for treatment of pulmonary embolism: A retrospective analysis

Abstract: Ultrasound-accelerated thrombolysis (USAT) is advocated in pulmonary embolism (PE) based on the hypothesis that adjunctive ultrasound provides superior clinical efficacy compared to standard catheter-directed thrombolysis (CDT). This retrospective study was designed to compare outcomes between the two modalities. We analyzed patients with computed tomography-diagnosed PE at our institution treated with either USAT or standard CDT. Efficacy parameters assessed included invasive pulmonary artery systolic pressur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
36
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 24 publications
1
36
0
Order By: Relevance
“…This well-done study is complementary to others revealing no short-term clinical outcomes differences in patients when CDT-US is used. Specifically, previous research has failed to find differences in in-hospital surrogate imaging outcomes, 8,9 and the current study 10 failed to find differences in in-hospital bleeding, ICH, and mortality outcomes. As Beyer et al 10 note, more studies, ideally randomized, are needed prior to more widespread use of CDT-US over CDT, particularly in this era of value-based care given that the former therapy carries substantially increased costs to the institution.…”
mentioning
confidence: 49%
See 1 more Smart Citation
“…This well-done study is complementary to others revealing no short-term clinical outcomes differences in patients when CDT-US is used. Specifically, previous research has failed to find differences in in-hospital surrogate imaging outcomes, 8,9 and the current study 10 failed to find differences in in-hospital bleeding, ICH, and mortality outcomes. As Beyer et al 10 note, more studies, ideally randomized, are needed prior to more widespread use of CDT-US over CDT, particularly in this era of value-based care given that the former therapy carries substantially increased costs to the institution.…”
mentioning
confidence: 49%
“…Studies comparing the two approaches to date have been single-center, retrospective, and modest in scope, with a focus on surrogate imaging outcomes related to echocardiographic comparisons of right ventricular function and pulmonary artery pressure changes. 8,9 It is in this context that, in this issue of CHEST, that Beyer et al 10 creatively utilized the 2016 National Readmissions Database (NRD) to examine nationwide, real-world utilization of systemic thrombolysis, CDT, and CDT-US, as well as to compare outcomes between CDT and CDT-US. The NRD is part of the Agency for Healthcare Research and Quality Healthcare Cost and Utilization Project all-payer family of databases.…”
mentioning
confidence: 99%
“…[19] In a recent retrospective study of PE, USAT and CDT were compared and PAP reduction, RV/ LV ratio, ICU stay, and bleeding rates were similar. [20] In the Paced Electrocardiogram Requiring Fast Emergent Coronary Therapy (PERFECT) study, PAP changes were similar in patients who underwent USAT and CDT for massive and submassive PE, but there was no significant comparison in the improvement of RVD. [21] In a retrospective study of 63 patients, no significant difference was found between USAT and CDT in terms of all clinical and hemodynamic parameters, mortality, and procedural complications at threemonth and one-year follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…This study was able to demonstrate that there were similar improvements in hemodynamics and length of ICU and hospital stays in both treatment groups. They also observed lesser bleeding complications and survival-to-discharge in patients receiving CDT [22]. One single center retrospective study done reviewed 60 patients between 2010 and 2016.…”
Section: Trialmentioning
confidence: 94%
“…Some studies done in the past few years, however, have shown similar results when comparing ultrasound CDT with standard CDT [21][22][23]. A retrospective study done compared patients with submassive and massive PE receiving either CDT or ultrasound CDT.…”
Section: Trialmentioning
confidence: 98%